Hitting all longest cycles in a graph - Fernandes, Cristina G.; Gutiérrez, Juan (Anais do Encontro de Teoria da Computação (ETC), 2017)
Let lct(G) be the minimum size of a set of vertices that contains at least one vertex in every longest cycle of a graph G. We show that lct(G) = 1 if G is a 3-tree, and that lct(G) ≤ 2 if G is a 2-connected partial 3-tree.